Identifikasi Kadar Hemoglobin Rendah Pada Calon Pendonor Darah Di Yogyakarta: Identification of Low Hemoglobin Levels in Prospective Blood Donors in Yogyakarta - Arif Tirtana; Lusia Peni Lamen; Wiwit Sepvianti; Aulia Rahman; Gravinda Widyaswara; Kumara Rahmawati Zain; Selasih Putri Isnawati Hadi (LPPM STIKES Guna Bangsa, 2025)
Hemoglobin (Hb) is influenced by several factors, including unhealthy lifestyle, age, gender, food and drink. Hb binds and carries oxygen from the lungs to be distributed to all body tissues. Hb deficiency can cause anemia which can cause morbidity and mortality for sufferers. This research is to determine the risk factors for low hemoglobin levels in potential donors. This research method is descriptive observational.